2014
DOI: 10.1530/ec-14-0096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D supplementation on physical performance and activity in non-western immigrants

Abstract: Vitamin D deficiency is highly prevalent among non-western immigrants in The Netherlands and associated with poor physical performance. The aim of this study was to assess the effect of vitamin D supplementation on physical performance, exercise capacity, and daily physical activity in vitamin D-deficient, overweight non-western immigrants. A randomized double-blind, placebo-controlled trial was conducted to assess the effect of vitamin D on physical performance. A total of 130 participants were included. Elig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…However, the results of this matter are more complex in young adults. Oosterwerff et al reported that daily vitamin D supplementation at doses of 1200 IU for 4 months had no beneficial effects on the physical performance or physical activity among overweight subjects aged between 20 and 65 years ( Oosterwerff et al, 2014 ). Inconsistently, a randomized, controlled trial showed that high doses of vitamin D (60,000 IU/week for 8 weeks followed by 60,000 IU/month for 4 months) combined with calcium supplementation significantly increased handgrip strength and walking distance in vitamin D-deficient Asian-Indians with a mean age of 31.5 ± 5.0 years ( Gupta et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of this matter are more complex in young adults. Oosterwerff et al reported that daily vitamin D supplementation at doses of 1200 IU for 4 months had no beneficial effects on the physical performance or physical activity among overweight subjects aged between 20 and 65 years ( Oosterwerff et al, 2014 ). Inconsistently, a randomized, controlled trial showed that high doses of vitamin D (60,000 IU/week for 8 weeks followed by 60,000 IU/month for 4 months) combined with calcium supplementation significantly increased handgrip strength and walking distance in vitamin D-deficient Asian-Indians with a mean age of 31.5 ± 5.0 years ( Gupta et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although chest pain is common in patients with CAD, it can be the most challenging symptom for healthcare providers to treat, and it can limit the quality of life by having a negative effect on health and economic systems (Izzo et al, 2012.;Qintar et al, 2017;Young & Melander, 2013). Assessing and correcting vitamin D levels may have additional cardiovascular benefits, including a reduction in chest pain that can improve the physiological response in the body, reduce negative cardiac events, and improve the quality of life of patients with CAD (Helde-Frankling et al, 2017;Oosterwerff et al, 2014). Alkhatatbeh et al (2019) proposed that low vitamin D levels, depression, and symptoms of anxiety could be complicit in the development of noncardiac chest pain.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, when 25(OH)D concentrations increased to > 60nmol/L, there was a borderline improvement in exercise capacity. The authors concluded that moderate doses of 25(OH)D supplementation did not significantly improve physical activity (30).…”
Section: The Journal Of Nutrition Health and Aging© J Nutr Health Agingmentioning
confidence: 97%
“…A study conducted by Oosterwerff et al (2014), that aimed to assess the effect of 25(OH)D supplementation on physical performance showed that the intervention group (age 20 -65 years) who received 1.200 IU vitamin D3 daily for 4 months did not improve physical performance. On the other hand, when 25(OH)D concentrations increased to > 60nmol/L, there was a borderline improvement in exercise capacity.…”
Section: The Journal Of Nutrition Health and Aging© J Nutr Health Agingmentioning
confidence: 99%